Description of the modified vestibular incision subperiosteal tunnel access (m-VISTA) technique in the treatment of multiple Miller class III gingival recessions: a case series - Aitziber Fernández-Jiménez; Ruth Estefanía-Fresco; Ana-María; Xabier Marichalar-Mendia; Luis-Antonio A (BMC, 2021)
Abstract Background Gingival recession is a common finding in the adult population. It is considered a challenge for clinicians to obtain a complete root coverage of Miller class III recession. The aim of this case series was to assess the outcomes achieved with the use of modified VISTA technique (m-VISTA) in patients having multiple Miller class III recessions after 6 months. Methods Ten patients (six women and four men; mean age: 53 years), who showed multiple Miller class III recessions (depth ≥ 2 mm) and who met the established inclusion and exclusion criteria, were treated by postgraduate students with the use of m-VISTA technique. Results A total of 38 recessions were performed. The recessions were mainly located in the mandible (80%), which included six molars. The mean baseline recession was 3.12 mm. Post the intervention, a mean root coverage of 58.72% was achieved, with complete root coverage observed in 29% of the recessions. Conclusions m-VISTA may offer several advantages in the treatment of Miller class III gingival recession. Nevertheless, more clinical trials with a longer follow-up period are needed to arrive at a concrete conclusion about its advantages. Trial registration: NCT03258996. Data registration: 08/18/2017.